The short-term effect of vitamin D supplementation on the response to muscle and liver damages indices by exhaustive aerobic exercise in untrained men: a quasi-experimental study - Vahid Parvizi Mastali; Rastegar Hoseini; Mohammad Azizi (BMC, 2022)
Abstract Background Exercise-induced muscle damage typically caused by unaccustomed exercise results in pain, soreness, inflammation, and muscle and liver damages. Antioxidant supplementation might be a useful approach to reduce myocytes and hepatocytes damages. Therefore, the present study was conducted to investigate the effect of short-term vitamin D (Vit D) supplementation on the response to muscle and liver damages indices by Exhaustive Aerobic Exercise (EAE) in untrained men. Methods In this clinical trial, 24 untrained men were randomly divided into experimental (Exp; n = 12) and control (C; n = 12) groups. Exp received 2000 IU of Vit D daily for six weeks (42 days), while C daily received a lactose placebo with the same color, shape, and warmth percentage. Two bouts of EAE were performed on a treadmill before and after six weeks of supplementation. Anthropometric characteristics (Bodyweight (BW), height, Body Fat Percentage (BFP), Body Mass Index (BMI), waist to hip ratio (WHR)) were measured at the Pre 1 and Pre 2. Blood samples were taken to measure the Creatine Kinase (CK), Lactate Dehydrogenase (LDH), Aspartate Aminotransferase (AST), Alanine Aminotransferase (ALT), Gamma-Glutamyl Transferase (GGT), Alkaline Phosphatase (ALP), and Vit D levels at four stages: Pre 1 (before the first EE session), Post 1 (after the first EE session), Pre 2 (before the second EE session), and Post 2 (after the second EE session). The data were analyzed using repeated-measures ANOVA, Bonferroni's post hoc test, independent t test, and dependent t-test at the significant level of P < 0.05 using SPSS version 26. Results The results show significant differences between Exp and C in alterations of BW (P = 0.039), BMI (P = 0.025), BFP (P = 0.043), and WHR (P = 0.035). The results showed that EAE increased muscle and liver damage indices and Vit D (P < 0.05). Compared with C, the results of the independent t-test showed significantly lower ALT (P = 0.001; P = 0.001), AST (P = 0.011; P = 0.001), GGT (P = 0.018; P = 0.001), and ALP (P = 0.001; P = 0.001); while significantly higher Vit D (P = 0.001, P = 0.001) in the Exp in both Pre 2 and Post 2; receptivity. The independent t test showed significantly lower ALT (P = 0.001; P = 0.001), AST (P = 0.011; P = 0.001), GGT (P = 0.018; P = 0.001), and ALP (P = 0.001; P = 0.001) and considerably greater Vit D (P = 0.001, P = 0.001) in the Exp in both Pre 2 and Post 2 compared to C. The results of an independent t test showed that LDH and CK levels in the Exp were significantly lower than those in the Post 2 (P = 0.001). Conclusions Short-term Vit D supplementation could prevent myocytes and hepatocytes damage induced by EAE.